The Thermal Background to Metamorphism - II: Simple Two-Dimensional Conductive Models - Fowler, C.; Nisbet, E. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1982)
Summary In a previous article simple one dimensional models of metamorphic conditions were examined. In this article more realistic two-dimensional models are set up, to show the metamorphic effects of burial, intrusion and thrusting. Models in which erosion takes place demonstrate the development of a metamorphic faciès series and underline the importance of understanding regional stratigraphy in interpreting metamorphism.